2007
DOI: 10.2139/ssrn.1017846
|View full text |Cite
|
Sign up to set email alerts
|

Agenda Setting, Public Opinion, and the Issue of Immigration Reform

Abstract: While the importance of agenda setting has been well-documented (Baumgartner and Jones 1995, Iyengar 1991), it is unclear whether its affect holds for issues that may not be salient to a significant portion of the public. We explore this puzzle by examining the issue of illegal immigration, as it is one policy that traditionally impacts those living in states along the U.S.-Mexico border more so than for those residing in non-border states. Our analyses of newspaper coverage of immigration and Gallup public o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…Berg 2009;Hopkins 2010;Rocha et al 2011). Media exposure, too, could play this role depending on the extent and tone of coverage on the issue (Dunaway et al 2010;Valentino et al 2012). Finally, the broader political context-both ''dramatic'' events such as terror attacks (Branton et al 2011) or longer-term reform efforts (Schildkraut 2012)-may affect the structure of individual choices.…”
Section: Resultsmentioning
confidence: 99%
“…Berg 2009;Hopkins 2010;Rocha et al 2011). Media exposure, too, could play this role depending on the extent and tone of coverage on the issue (Dunaway et al 2010;Valentino et al 2012). Finally, the broader political context-both ''dramatic'' events such as terror attacks (Branton et al 2011) or longer-term reform efforts (Schildkraut 2012)-may affect the structure of individual choices.…”
Section: Resultsmentioning
confidence: 99%
“…Other scholars have found that the rallies did have important agenda-setting effects that shifted voters' attitudes, particularly towards the foreign-born. For example, Dunaway, Abrajano, and Branton's (2007) research showed that the protests increased the media's attention to, and heightened the general public's perception of, the issue of immigration. Using exit-poll data from three different states, Cohen-Marks, Nuno, and Sanchez (2008, 708) found that the marchers' efforts to include pro-American messages did not improve perceptions of Mexican immigrants, particularly among whites, conservatives, and Republicans.…”
Section: Time Space and The Effects Of Protests On Public Opinionmentioning
confidence: 99%
“…When reporting issues, the media add emphasis to some of these (Sheafer, 2007). The coverage of issues by the media has an effect, but the level of salience that an issues gains varies from one issue to another (Dunaway, Branton and Abrajano, 2010;Walgrave, Soroka, Nuytemans, 2008).…”
Section: Agenda Settingmentioning
confidence: 99%